Engineering a Smart Agent for Enhanced Immunotherapy Effect by Simultaneously Blocking PD‐L1 and CTLA‐4 - Jiang, Chunjuan; Zhang, Le; Xu, Xiaoping; Qi, Ming; Zhang, Jianping; He, Simin; Tian, Qiwei; Song, Shaoli (Advanced science, 2021)
Combinations of immune checkpoint therapies show encouraging results in the treatment of many human cancers. However, the higher costs and greater side effects of such combinations compared with single‐agent immunotherapies limit their further applications. In this work, a novel smart agent, KN046@19F‐ZIF‐8, is developed to overcome these limitations. KN046 is a novel recombinant humanized PD‐L1/CTLA‐4 bispecific single‐domain antibody‐Fc fusion protein, which can bind to both PD‐L1 and CTLA‐4 effectively. ZIF‐8 is a smart delivery system, which can safely and effectively deliver KN406 to a tumor. In vitro and in vivo results demonstrate that the smart agent KN046@19F‐ZIF‐8 not only improves the immune response rate of the antibody drug in treatment of tumors but also reduces its toxic side effects, thereby achieving excellent antitumor efficacy. This study provides an engineering strategy for clinical applications of a more effective immunotherapy. A novel smart agent is engineered by coating a tumor microenvironment responsive ZIF‐8 on the novel recombinant humanized PD‐L1/CTLA‐4 bispecific single‐domain antibody‐Fc fusion protein to overcome the higher costs and greater side effects of single‐agent immunotherapies.